SOS BURNS: Aplicativo móvel para auxílio no atendimento das vítimas de queimaduras - Lazaro, Hudson Alex [UNIFESP] (2018)
Introduction: Burn injuries in Brazil are a public health problem. It is estimated that two million people each year suffer this injuries. A lot of these burn victims are treated by non especialists that need more information about burn treatment. The use of smartphones has represented a solution to spread specific information to healthcare professionals, by means of medical applications. The development of a mobile application to treat burns is expected to contribute to decrease the victims’ morbimortality, therefore causing a great social and economic impact to the public health. Aim: To develop a mobile application which will support the health care professionals in the treatment of burn victims. Methods For the application content, were used Design Thinking methodology and “Projeto Canvas” to definition of the app content, and also an Android Studio™ development tool was used for the application elaboration. Results: The content was based on the main topics which should be known by the healthcare professional who will handle the basic care to the burn patient. The application also was developed introducing a bidimensional tool where the calculation of the burned body surface and the volemic correction the patient needs at the first 24 hours of caring were carried out.. The application is already available at the Google Play ™ store. Conclusion: The SOS BURNS application was created as a support tool for the healthcare professionals who deal with the burning victims care.